A novel, stiff-shaft, flexible-tip guidewire for cannulation of biliary stricture during endoscopic retrograde cholangiopancreatography: a randomized trial - Albert, Jörg G.; Lucas, Katja; Filmann, Natalie; Herrmann, Eva; Schröder, Oliver; Sarrazin, Christoph; Trojan, Jörg; Kronenberger, Bernd; Bojunga, Jörg; Zeuzem, Stefan; Friedrich-Rust, Mireen (Endoscopy, 2014)
Background and study aims: During endoscopic retrograde cholangiopancreatography (ERCP), a guidewire is used to cannulate biliary strictures and allow for therapeutic interventions. The aim of this study was to assess the success of stricture cannulation using a combination of a flexible guidewire and a stable nitinol wire vs. a novel, single, stiff-shaft, flexible-tip guidewire.Patients and methods: Consecutive patients who were scheduled for ERCP for biliary obstruction were randomized to undergo the procedure with either a 260-cm long, angled-tip hydrophilic wire in combination with a nitinol wire as required (standard group), or a novel, 270-cm guidewire featuring a hyperflexible, hydrophilic tip with a stiff shaft (novel group). At unsuccessful negotiation of the stricture, patients in the standard group were switched to the novel guidewire and vice versa (“crossover”). Successful cannulation (primary success: as assigned; final success: after “crossover”), procedure time, and total number of wires needed per procedure were compared.Results: A total of 222 patients were randomized and 197 were included in the study (97 in the standard group and 100 in the novel group). The primary success rate was significantly higher in the novel group (94/100, 94 %) compared with the standard group (77/97, 79 %; P = 0.00041), and final success was similar. Mean time (median, interquartile range) to stricture cannulation was 11.2 minutes (6.3, 3.7 – 14.6) in the standard group and 8.1 minutes (2.5, 0.9 – 7.7) in the novel group (P < 0.0001). The mean total procedure time was 31.2 minutes (24.6, 16.5 – 40.8) vs. 24.3 minutes (16.9, 10.0 – 31.5), respectively (P = 0.0011). There were no complications observed with either of the guidewires.Conclusions: A guidewire that features a flexible tip with a stable shaft could replace the use of a combination of flexible and stable guidewires and increase the success rate of stricture cannulation while decreasing the procedure time.ClinicalTrials.gov Identifier: NCT 01382680